POLYMORPHISM OF HOMO SAPIENS GENOTYPE AND PHENOTYPE AS ONE OF THE CAUSES OF LIMITATION OF LABORATORY IMMUNOLOGICAL DIAGNOSIS - O. L. Kolesnikov; I. I. Dolgushin; G. A. Selyanina; A. A. Kolesnikova (Медицинская иммунология)
Abstract. Presence of significant genotypic and phenotypic variability in Homo sapiens species has been shown. According to the findings published in the world literature there were demonstrated differences in the referent meanings of blood lymphocyte content in persons of different races. As a result values considered normal for one population might be found abnormally high as well as abnormally low for another population. By means of comparing our own findings with immunological standards for the Russian Federation there were shown differences specific for various regions. It has been suggested to develop and implement a countrywide program to identify the values corresponding to the norm for different regions of Russia and different age groups.